ANTIMICROBIAL ACTIVITY OF CERAMIC DISKS LOADED WITH SILVER IONS AND NITROXOLINE - DANISTEAN, Ancuta; GOREA, Maria; AVRAM, Alexandra; RAPUNTEAN, Sorin; TOMOAIA, Gheorghe; MOCANU, Aurora; ISTRATE (GARBO), Corina; HOROVITZ, OSSI; TOMOAIA-COTISEL, Maria (Studia Universitatis Babeș-Bolyai Chemia, 2016)
Ceramic porous disks made of hydroxyapatite, HAP, loaded with silver ions and nitroxoline (5-nitro-8-hydroxyquinoline, NHQ) are used in vitro against pathogens, such as Staphylococcus aureus. HAP powder was synthesized by a wet chemical method, and its phase purity and nanocrystalline structure were assessed by X-ray diffraction (XRD), transmission electron microscopy (TEM) and atomic force microscopy (AFM). Disk samples of HAP were prepared and impregnated with Ag+ ions and NHQ solutions. A strong antimicrobial activity of all samples was assessed by the diffusion assay in vitro against Staphylococcus aureus. Through the development of the optimal composition of these biomaterials, this approach might hold potential applications for antimicrobial coating, bone tissue engineering scaffolds and biomedical devices.